Pengaruh Pembelajaran Kontekstual terhadap Hasil Belajar dalam Pembelajaran Pendidikan Pancasila Kelas IV SDN 06 Pontianak Utara - Khairunnisa, Khairunnisa; Salimi, Asmayani; Ghasya, Dyoty Auliya Vilda (AS-SABIQUN, 2023)
This study aims to describe the Effect of Contextual Learning on Learning Outcomes in Pancasila Education Learning Class IV SDN 06 North Pontianak. The research method used is an experimental method with a quasi-experimental design and nonequivalent control group research plan. A sample of 47 students used a purposive sampling technique. In collecting research data using measurement techniques and data collection tools in research is a written test. The results of the study can be concluded that: The learning outcomes of the control class and the experimental class in learning Pancasila education with the calculation of data analysis in the experimental class with an average pre-test score of 43.77 and a post-test average score of 77. In the control class the score average student learning outcomes pre-test 51.9 and post-test 56.8. There are differences in learning outcomes in the experimental class and control class by testing the normality known pre-test and post-test data Xcount ≤ Xtable = 7.815, then the data is normally distributed. Apart from that, the researchers also carried out a homogeneity of variance test, from the results obtained Fcount ≤ Ftable = 2.024. There is an effect of contextual learning on the learning outcomes of class IV Pancasila education is the polled variance formula, namely t-test (Polled Variance) at level = 5% and (dk =〖n〗_(1+) n_2-2= 45) obtained t_(count > ) t_table or 8.5 > 2.0. Then the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This means that there is an influence of contextual learning on the learning outcomes of Pancasila education. Post test data calculated using the effect size formula was obtained at 1.17 with high criteria. This proves that the application of contextual learning has a high influence on the learning outcomes of Pancasila class IV SDN 06 Pontianak Utara.